Rural Citizen, Urban Tourist – the Example of Tourists from Rural Areas Visiting Kraków - Seweryn, Renata; Niemczyk, Agata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The combination of the terms „countryside” and „tourism” is usually associated with the use of rural areas or activating them for the purpose of tourism. However, the tourist activity of rural dwellers is rarely analysed. The purpose of this article is to try to answer the following question: How do tourists coming from rural areas to cities differ from visitors who come from urban areas? With the use of information obtained from the study of tourist traffic in Kraków, Poland, statistically significant differences in the behaviour of these two groups visiting the city in 2017 were determined. The empirical analyses are preceded by a review of Polish and foreign literature on tourist activity and its determinants, on urban tourism and on the functioning of the modern countryside. The results show that rural dwellers, more frequently than their urban counterparts, take shorts visits to cities and use the services of tour operators.